2022
DOI: 10.3390/cancers14061404
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Proton Pump Inhibitors and Histamine-2-Receptor Antagonists on Non-Small Cell Lung Cancer Immunotherapy: A Systematic Review and Meta-Analysis

Abstract: (1) Background: In recent years, immunotherapy has revolutionized the treatment landscape of non-small cell lung cancer (NSCLC), representing a therapeutic breakthrough in this field. Antacid agents such as proton pump inhibitors (PPIs) and histamine-2-receptor antagonists (H2RAs) are commonly prescribed for extended periods in NSCLC patients, and these drugs have the potential to modify the efficacy of immune checkpoint inhibitors (ICIs). (2) Materials and Methods: Herein, we conducted a systematic review and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 47 publications
1
47
0
Order By: Relevance
“…(2) Proton pump inhibitors (PPIs): Antacids such as PPIs are often used in cancer patients, and these drugs have the potential to alter GM and the efficacy of anti-tumor therapy ( 96 , 97 ). Two meta-analyses demonstrated that concomitant antacid could alter the activity of ICIs, PPIs were inversely associated with progression free survival and overall survival ( 98 , 99 ). (3) Prognosis: By measuring the abundance and diversity of GM, we can quantify the relative proportions of recognized “beneficial” or “harmful” bacteria, which can predict treatment outcomes and prognosis, and help guide treatment decisions and regimens.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Proton pump inhibitors (PPIs): Antacids such as PPIs are often used in cancer patients, and these drugs have the potential to alter GM and the efficacy of anti-tumor therapy ( 96 , 97 ). Two meta-analyses demonstrated that concomitant antacid could alter the activity of ICIs, PPIs were inversely associated with progression free survival and overall survival ( 98 , 99 ). (3) Prognosis: By measuring the abundance and diversity of GM, we can quantify the relative proportions of recognized “beneficial” or “harmful” bacteria, which can predict treatment outcomes and prognosis, and help guide treatment decisions and regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Antacid agents such as proton pump inhibitors (PPIs) and histamine-2-receptor antagonists (H2RAs) are commonly prescribed for extended periods in urological cancer patients. Recent evidence also suggested that PPI usage in patients with advanced NSCLC receiving ICI therapy was associated with an increased mortality risk ( Qin et al, 2021 ; Rizzo et al, 2022 ; Wei et al, 2022 ). However, the relationship between antacid use and ICI outcomes in urological cancer patients remains controversial due to a lack of comprehensive evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic therapy for non-small cell lung cancer has shown considerable progress for the past two decades, which is due to the development of new drugs, especially small molecule tyrosine kinase inhibitors and immune checkpoint inhibitors [1][2][3]. Therefore, systemic therapy is determined by mutations in driver oncogenes and immune checkpoint protein expression, in addition to individual factors.…”
Section: Introductionmentioning
confidence: 99%